Ameliorative and antioxidant effects of myrtle berry seed (Myrtus communis) extract during reflux-induced esophagitis in rats. (1st September 2016) - Jabri, Mohamed-Amine; Tounsi, Haifa; Rtibi, Kais; Marzouki, Lamjed; Sakly, Mohsen; Sebai, Hichem
Abstract: Context Myrtle, Myrtus communis L. (Myrtaceae), is a medicinal plant well known for its richness in phenolic compounds and its beneficial effects for the treatment of gastrointestinal disorders. Objective In the present work, the protective effect of the myrtle berry seed aqueous extract (MBSAE) against esophageal reflux (ER)-induced damage in esophagus mucosa as well as the mechanisms implicated was determined. Materials and methods In this respect, adult male Wistar rats were used and divided into seven groups: Control, ER, ER + various doses of MBSAE, ER + famotidine or ER + gallic acid. The ER was induced and animals were per orally (p.o.) treated with MBSAE or reference molecules during 6 h. The phytochemical screening was determined using colourimetric analysis. Results MBSAE is rich in total polyphenols and anthocyanins and exhibited an important in vitro antioxidant activity. In vivo, we firstly found that ER led to marked macroscopic and histopathological changes in esophagus. The results showed, also, that the ER was accompanied by a state of oxidative stress as assessed by an increase of lipid peroxidation, a decrease of the sulphhydryl groups and glutathione levels, as well as antioxidant enzyme activities depletion. MBSAE abrogated all morphological, histopathological and biochemical alterations. We showed also that ER increased esophageal calcium, hydrogen peroxide (H2 O2 ) and free iron levels while MBSAE treatment protected against intracellular mediators deregulation. Conclusion Our data suggest that MBSAE exerted a potential protective effect against ER-induced damage in rat esophagus, at least in part, due to its antioxidant properties.